Structural-phase changes in thin films and surface layers of Ti41.5Zr41.5Ni17 alloy, stimulated by radiation-thermal impact of hydrogen plasma - Malykhin, S.V.; Makhlai, V.A.; Surovitskiy, S.V.; Borisova, S.S.; Herashchenko, S.S.; Kondratenko, V.V.; Kopylets, I.A.; Baturin, A.A.; Terentyev, D. (Вопросы атомной науки и техники, 2019)
X-ray diffraction and SEM microscopy were used to study structural and phase changes in the surface layers of a Ti41.5Zr41.5Ni17 alloy bulk sample (target) and a thin film (deposited by magnetron sputtering of the target) under radiation-thermal action of pulsed hydrogen plasma with a thermal load of 0.6 MJ/m² in QSPA Kh-50 installation. It is established that the irradiation results in the formation of a two-phase state: the icosahedral quasicrystalline phase together with the phase of the 1/1 approximant crystal (W-phase). As a result of isothermal (550°C) annealing, the content of the quasicrystalline phase increases. Методами рентгенівської дифракції та SEM-мікроскопії вивчені структурні і фазові зміни в поверхневих шарах масивного зразка (мішені) сплаву Ti41.5Zr41.5Ni17 і тонкої плівки, отриманої магнетронним розпиленням мішені, при радіаційно-термічному впливі імпульсною водневою плазмою з тепловим навантаженням 0,6 MДж/м² на КСПП Х-50. Встановлено, що в результаті опромінення формується двофазний стан: ікосаедрична квазікристалічна фаза спільно з фазою кристала-апроксиманта 1/1 (W-фаза). В результаті ізотермічного (550°C) відпалу зміст квазікристалічної фази збільшується. Методами рентгеновской дифракции и SEM-микроскопии изучены структурные и фазовые изменения в поверхностных слоях массивного образца (мишени) сплава Ti41.5Zr41.5Ni17 и тонкой пленки, полученной магнетронным распылением мишени, при радиационно-термическом воздействии импульсной водородной плазмой с тепловой нагрузкой 0,6 MДж/м² на КСПУ Х-50. Установлено, что в результате облучения формируется двухфазное состояние: икосаэдрическая квазикристаллическая фаза совместно с фазой кристалла-аппроксиманта 1/1 (W-фаза). В результате изотермического (550°C) отжига содержание квазикристаллической фазы увеличивается.